Pediatric Moyamoya Disease and Syndrome in Italy: A Multicenter Cohort - Po', Chiara; Nosadini, Margherita; Zedde, Marialuisa; Pascarella, Rosario; Mirone, Giuseppe; Cicala, Domenico; Rosati, Anna; Cosi, Alessandra; Toldo, Irene; Colombatti, Raffaella; Martelli, Paola; Iodice, Alessandro; et al. (Frontiers in Pediatrics, 2022)
Background. Moyamoya is a rare progressive cerebral arteriopathy, occurring as an isolated phenomenon (moyamoya disease, MMD) or associated with other conditions (moyamoya syndrome, MMS), responsible for 6%-10% of all childhood strokes and transient ischemic attacks (TIAs). Methods. We conducted a retrospective multicenter study on pediatric-onset MMD/MMS in Italy, in order to characterize disease presentation, course, management, neuroradiology and outcome in a European country. Results. 65 patients (34/65 females) with MMD (27/65) or MMS (38/65) were included. 18% (12/65) were asymptomatic and diagnosed incidentally during investigations performed for an underlying condition (incMMS), whereas 82% (53/65) patients with MMD or MMS were diagnosed due to the presence of neurological symptoms (symptMMD/MMS). Of these latter, before diagnosis 66% (43/65) suffered from cerebrovascular events with or without other manifestations (ischemic stroke 42%, 27/65; TIA 32%, 21/65; no hemorrhagic strokes), 18% (12/65) reported headache (in 4/12 headache was not associated with any other manifestation), and 26% (17/65) experienced multiple phenotypes (≥2 among: stroke/TIA/seizures/headache/other). Neuroradiology disclosed ≥1 ischemic lesion in 67% (39/58), and posterior circulation involvement in 51% (30/58). 73% (47/64) of patients underwent surgery and 69% (45/65) received aspirin, but after diagnosis further stroke events occurred in 20% (12/61), including operated patients (11%, 5/47). Between symptom onset and last follow-up, the overall patient/year incidence of stroke was 10.26% (IC 95% 7.58-13.88%). At last follow-up (median 4 years after diagnosis, range 0.5-15), 43% (26/61) patients had motor deficits, 31% (19/61) intellectual disability, 13% (8/61) epilepsy, 11% (7/61) behavioral problems; 25% (13/52) had mRS>2. The proportion of final mRS>2 was significantly higher in symptMMD/MMS than in incMMS patients (p=0.021). Onset age <4 years and stroke before diagnosis were significantly associated with increased risk of intellectual disability (p=0.0010 and p=0.0071, respectively), and mRS>2 at follow-up (p=0.0106 and p=0.0009, respectively). Conclusions. Moyamoya is a severe condition that may affect young children and frequently cause cerebrovascular events throughout the disease course, but may also manifest with multiple and non-cerebrovascular clinical phenotypes including headache (isolated or associated with other manifestations), seizures, and movement disorder. Younger onset age and stroke before diagnosis may associate with increased risk of worse outcome (final mRS>2).